2019
DOI: 10.3390/su11051234
|View full text |Cite
|
Sign up to set email alerts
|

Residential Consumers’ Willingness to Pay Price Premium for Renewable Heat in South Korea

Abstract: Heat accounts for about one-third of the final energy use and it is mostly produced using fossil fuels in South Korea. Thus, heat production is an important source of greenhouse gas emissions. However, using renewable heat that is directly produced from renewable energy, such as bioenergy, geothermal, or solar heat can save energy and reduce greenhouse gas emissions, rather than transforming conventional fuel into heat. Therefore, an energy policy for renewable heat urgently needs to be established. It is such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The single bounded procedure is easier to implement than the double bound, in particular, in data collection and estimation. On the other hand, the double bound is well known to be more efficient than the single bound estimator, despite certain inconsistency issues [50]. Moreover, Calia and Strazzera [49] found out that the difference between the two approaches tends to reduce as the sample size is increased and is often negligible for medium size samples (over 250 observations), in particular, if adequately pre-tested.…”
Section: Contingent Valuation and The Survey Designmentioning
confidence: 99%
“…The single bounded procedure is easier to implement than the double bound, in particular, in data collection and estimation. On the other hand, the double bound is well known to be more efficient than the single bound estimator, despite certain inconsistency issues [50]. Moreover, Calia and Strazzera [49] found out that the difference between the two approaches tends to reduce as the sample size is increased and is often negligible for medium size samples (over 250 observations), in particular, if adequately pre-tested.…”
Section: Contingent Valuation and The Survey Designmentioning
confidence: 99%
“…Biomethane was preferred over SNG despite the 'food vs. fuel' debate, which is tightly connected to bio-based energy carriers [28]. Kim et al reported that South Korean households would accept a 5% price premium for renewable heat over fossil heat [29] regardless of the renewable source. Another study from South Korea revealed a 32% willingness to pay (WTP) for renewable heat based on biomethane [30].…”
Section: Introductionmentioning
confidence: 99%